Analysis of a solar air heater for augmented thermohydraulic performance using helicoidal spring shaped fins-A numerical study. (November 2020) - Arunkumar, H.S.; Kumar, Shiva; Karanth, K. Vasudeva
Abstract: This study presents the performance analysis of solar air heater in which spring shaped fins introduced beneath the absorber plate are investigated. Effects of spring fin wire diameter ratio, spring diameter ratio and helicoidal pitch ratio on the thermal performance for varying flow rates are analyzed. The results for thermo-hydraulic enhancement factor are studied and it is found that the spring fin produces greater turbulence inside the absorber duct while causing lesser resistance to flow. For varying helicoidal pitch ratio of spring fin, the Thermo-hydraulic enhancement factor and Nusselt number are found to be optimally high for a helicoidal pitch ratio of 0.133 for the entire range of Reynolds numbers. The Nusselt number rises with increase in spring wire diameter ratio. However, the thermo-hydraulic enhancement factor rises with increase in spring wire diameter ratio up to 0.093 and then drops due to higher flow resistance. The Nusselt number drops with increase in helicoidal spring diameter ratio. The thermo-hydraulic enhancement factor is substantially higher at 1.268 for helicoidal spring diameter ratio of 0.06 at lower Reynolds numbers. Correlations are developed for the spring geometric parameters in terms of Nusselt number and friction factor with a deviation of ± 10 % in terms of parity. Highlights: 3D numerical simulation to evaluate the performance of configurations with different parameters of spring fins in SAH. Experimental data to validate the numerical CFD simulation. The correct parameters of spring fins for improving the thermo-hydraulic performance. Correlations developed for the spring geometric parameters in terms of Nusselt number and friction factor.